2018
DOI: 10.3389/fgene.2018.00668
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Identifies a Novel Variation of WAS Gene Coordinating With Heterozygous Germline Mutation of APC to Enhance Hepatoblastoma Oncogenesis

Abstract: Hepatoblastoma (HB), a leading primary hepatic malignancy in children, originates from primitive hepatic stem cells. This study aimed to uncover the genetic variants that are responsible for HB oncogenesis. One family, which includes the healthy parents, and two brothers affected by HB, was recruited. Whole-genome sequencing (WGS) of germline DNA from all the family members identified two maternal variants, located within APC gene and X-linked WAS gene, which were harbored by the two brothers. The mutation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The sequencing methods used were highly variable across the studies ( Table 3 and Supplementary Data 1:T1). Of the studies in this review, 10 indicated that they used one or more forms of NGS sequencing (whole-exome, whole-genome, RNA-seq) and thus were able to sample CH variants broadly (Valentine et al, 2014;Spinella et al, 2015;Zhang et al, 2015Zhang et al, , 2018Diets et al, 2018;Diness et al, 2018;Gröbner et al, 2018;Waszak et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019). Thirteen studies indicated that they used non-NGS methods (Sanger, Direct sequencing, SNP-array, Multiplex ligation-dependent probe amplification) and were therefore limited in the number of genes and CH variants analyzed (Quesnel et al, 1999;De Rosa et al, 2000;Østergaard et al, 2005;Okkels et al, 2006;Scott et al, 2007;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Piane et al, 2016;Svojgr et al, 2016;Moriyama et al, 2017;Sharapova et al, 2018).…”
Section: Methodsologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
See 3 more Smart Citations
“…The sequencing methods used were highly variable across the studies ( Table 3 and Supplementary Data 1:T1). Of the studies in this review, 10 indicated that they used one or more forms of NGS sequencing (whole-exome, whole-genome, RNA-seq) and thus were able to sample CH variants broadly (Valentine et al, 2014;Spinella et al, 2015;Zhang et al, 2015Zhang et al, , 2018Diets et al, 2018;Diness et al, 2018;Gröbner et al, 2018;Waszak et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019). Thirteen studies indicated that they used non-NGS methods (Sanger, Direct sequencing, SNP-array, Multiplex ligation-dependent probe amplification) and were therefore limited in the number of genes and CH variants analyzed (Quesnel et al, 1999;De Rosa et al, 2000;Østergaard et al, 2005;Okkels et al, 2006;Scott et al, 2007;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Piane et al, 2016;Svojgr et al, 2016;Moriyama et al, 2017;Sharapova et al, 2018).…”
Section: Methodsologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
“…One study used evidence from RNA-seq data that the alternate alleles were on different chromosomes (Zhang et al, 2015). All other studies that performed phasing used sequence data from the patient and his/her parent(s) (i.e., Mendelian inheritance; Quesnel et al, 1999;De Rosa et al, 2000;Okkels et al, 2006;Scott et al, 2007;Peters et al, 2009;Majumdar et al, 2010;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Valentine et al, 2014;Spinella et al, 2015;Piane et al, 2016;Svojgr et al, 2016;Diets et al, 2018;Diness et al, 2018;Salih et al, 2018;Sharapova et al, 2018;Zhang et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019).…”
Section: Methodsologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent mutations in CTNNB1 and increased expression of the transcription factor NFE2L2 have been reported in HB [14]. Mutations in other components of the beta-catenin degradation complex, including those affecting APC and Axin have also been reported [19,64,65]. Beta-catenin-mediated expression of hepatic stem/progenitor markers and interplay of Wnt/beta-catenin and Myc signaling have been observed in aggressive HB [13].…”
Section: Wnt/beta-catenin Signaling In Hbmentioning
confidence: 99%